THE EFFECT OF BENZONAL ON INDICATORS OF ENDOGENOUS INTOXICATION IN CHILDREN WITH ACUTE PNEUMONIA AT AN EARLY AGE - Fatima F. Xoltayeva (Scholar Express Journals, 2023)
Acute pneumonia in young children continues to be a pressing problem, due to the significant prevalence and frequency of this pathology. According to WHO, pneumonia accounts for 3-4% in developed countries, and 10-20% per year in developing countries. According to the Ministry of Health of the Republic of Uzbekistan, acute respiratory diseases and pneumonia account for 50-60% of all morbidity in children. Attention to the problem of pneumonia is also explained by the very high mortality rate. This group of diseases ranks first among the causes of mortality in children.
Keywords: Pneumonia; pulmonology; endogenous diseases